CLASSROOM PRACTICES FOR TEACHING IDIOMS TO THE ENGLISH LANGUAGE LEARNERS - Bektursyn Bayan; Karbozova Gulnara Kumisbekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Idioms can be confusing for English Language Learners. An idiom is “an expression that cannot be understood from the meanings of its separate words but that has a separate meaning of its own” according to Learners Dictionary. Once ELLs understand that some phrases in English are idioms, they can be on the lookout for them and will gain a clearer understanding of the English Language.